The Artificial Heart Juggernaut - Gil, Gideon (The Hastings Center report, 1989)
Permanent implants of artificial hearts have been halted by bad results, but questions about fairness and informed consent have failed to stop manufacturers, surgeons, and hospitals from using mechanical hearts as bridges to transplant.